Eatsarapph: An implementation of E-commerce framework with route analytics - CHRISTIAN ALFRED M. VILLENA; JASMIN D. NIGUIDULA; JENNIFER B. ENRIQUEZ (Journal of Advanced Research in Social Sciences and Humanities, 2017)
Aim: The study’s goals are i) to create an online restaurant ordering system that uses an e-commerce framework and (ii) to develop a client-side application that displays restaurants according to the diner’s preferences in terms of cuisine type.Methodology: The correct steps of the System Development Life Cycle, including planning, analysis, design, implementation, and maintenance, were followed in this paper. The information was gathered by secretly watching patrons at various eateries.Findings: Eatsarap is a mobile app developed digitally. It has been successfully planned and implemented that PH will be used. EatsarapPH was built on an e-commerce infrastructure to facilitate transactions between diners and eateries.Implications/Novelty: The app makes life easier for diners and eateries by streamlining the ordering process, managing the menu, and processing payments online. This innovative layout benefits both diners and establishment owners.